2016
DOI: 10.1007/s12663-016-0902-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ropivacaine 0.75 % and Lignocaine 2 % with 1:200,000 Adrenaline in Dental Extractions: Single Blind Clinical Trial

Abstract: SDC/MISC/2013/239.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In our study, none of the participants from either group experienced any pain throughout the procedure, but they withstood the procedure well with comfort, indicating adequate pain control. These findings are similar to those of other studies, such as Budharapu et al [ 1 ], Bansal et al [ 14 ], Brković et al [ 20 ], and Reddy et al [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, none of the participants from either group experienced any pain throughout the procedure, but they withstood the procedure well with comfort, indicating adequate pain control. These findings are similar to those of other studies, such as Budharapu et al [ 1 ], Bansal et al [ 14 ], Brković et al [ 20 ], and Reddy et al [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…The onset of anesthesia for lignocaine and ropivacaine varied from 1 to 2 min and 2 to 3 min, respectively, indicating that 2% lignocaine hydrochloride had the quickest onset of anesthesia. In a similar study by Reddy KV et al [ 4 ] and Bansal V et al [ 14 ], lignocaine was faster to act compared to ropivacaine. In our study, the mean onset of anesthesia was statistically insignificant for the ropivacaine group compared with the lignocaine with adrenaline group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a randomized single-blind study, Bansal and Kumar in terms of quality of anesthesia had reported that ropivacaine 0.75% had a longer duration of action and effective diffusion property than that of lignocaine 2% with adrenaline 1:200000. Additionally, in our study, a comparison of VAS scores at different time points between the two groups demonstrated that the scores in the ropivacaine group were consistently lower than those in the lignocaine group [ 13 ]. Furthermore, the difference in the scores was statistically significant at all time points.…”
Section: Discussionmentioning
confidence: 97%
“…The authors conducted a randomized clinical trial involving 50 patients undergoing maxillofacial surgery and concluded that ketoprofen transdermal patch was slightly better than diclofenac transdermal patch with respect to analgesic efficacy. The authors should be applauded for performing a well-designed study in an important topic (e.g., acute pain) in patients undergoing elective surgery [2,3]. The need to improve postoperative recovery by reducing moderate/severe postoperative pain makes the topic very important in maxillofacial surgery [4,5].…”
mentioning
confidence: 99%